Paleoceanography of the northwestern Pacific across the Early–Middle Pleistocene boundary (Marine Isotope Stages 20–18) - Kubota, Yoshimi; Haneda, Yuki; Kameo, Koji; Itaki, Takuya; Hayashi, Hiroki; Shikoku, Kizuku; Izumi, Kentaro; Head, Martin J.; Suganuma, Yusuke; Okada, Makoto (Progress in earth and planetary science, 2021)
The fluctuating position of the boundary between the Kuroshio (warm) and Oyashio (cold) currents in the mid-latitude western North Pacific affects both heat transport and air–ocean interactions and has significant consequences for the East Asian climate. We reconstruct the paleoceanography of Marine Isotope Stages (MIS) 20–18, MIS 19 being one of the closest astronomical analogues to the present interglacial, through multiple proxies including microfossil assemblage data, planktonic foraminiferal isotopes (δ 18 O and δ 13 C), and foraminiferal Mg/Ca-based temperature records, from the Chiba composite section (CbCS) exposed on the Boso Peninsula, east-central Japan. Principal component analysis (PCA) is used to capture dominant patterns of the temporal variation in these marine records, and shows that the relative abundances of calcareous nannofossil and radiolarian taxa are consistent with the water mass types inferred from geochemical proxies. The leading mode (36.3% of total variance) mirrors variation in the terrestrial East Asian winter monsoon (EAWM), reflecting seasonal trends dominated by the winter monsoon system. In the CbCS, this mode is interpreted as reflecting the interplay between the warm Kuroshio and cold Oyashio waters, which is likely related to the latitudinal shift of the subtropical–subarctic gyre boundary in the North Pacific. The second mode (15.4% of total variance) is closely related to subsurface conditions. The leading mode indicates that MIS 19b and 19a are represented by millennial-scale stadial/interstadial oscillations. Northerly positions for the gyre boundary during late MIS 19c, the interstadials of MIS 19a, and early MIS 18 are inferred from the leading mode, which is consistent with a weak EAWM and consequent mild winter climate in East Asia. Nonetheless, the northerly positions for the gyre boundary during late MIS 19c and early MIS 19a were not associated with subsurface warming presumably due to the suppressed gyre circulation itself caused by the weak Aleutian Low. Intermittent southerly positions for the gyre boundary are inferred for the stadials of MIS 19b and 19a. Regional sea surface temperature (SST) comparisons in the western North Pacific reveal that the moderate SSTs during MIS 19a through early MIS 18 were restricted to the mid- to high latitudes, influenced by the weak EAWM. Comparison between MIS 20–18 and MIS 2–1 suggests that glacial MIS 20 and 18 had significantly milder winters than MIS 2, likely related to the relatively weak EAWM.